Social Factors Associated With Alcohol Consumption Among the Youth in Acholi Quarters - Tina Naume (Uganda Christian University, 2025)
This study focused on the “Social factors associated with alcohol consumption among the youth in Acholi Quarters”. Objectives; To explore the relationship between peer influence on alcohol consumption among the youth in Acholi Quarters, To explore the relationship between family dynamics and alcohol consumption among youths in Acholi quarters and To explore the availability and accessibility of alcohol consumption among youth in Acholi Quarters. Theory. Social learning theory of Albert Bandura (1977) which urges that learning behaviours is through observation and imitating the role models which the youths in Acholi quarters used. Study design. The case study design was used for this study. Method. The interview guide was used by the researcher as it favours qualitative research (Creswell, 2012). Source of data. Data 20 respondents and all were residents of Acholi Quarters in Banda. Findings. The religious findings showed that Christians were dominant in Acholi quarters with 12 respondents in total, 0 Moslems, 4 Catholics and 4 respondents belonged to other religions. The markets and friends were the dominant sources of alcohol that the youths consumed. Waragi, vodica and siminorf were the common alcoholic drinks the youths used to consume. All the respondents approved the peer influences to be the greatest influential factors for the youths to consume alcohol. The family dynamics like family conflicts and parental authorities highly determined alcohol consumption among the youths. Conclusion. The researcher concluded that religious leaders should engage themselves in fighting alcohol consumption among the youths because the finds showed that families of religious parents had low risks of their youths consuming alcohol. The researcher recommendations. The government of Uganda has been putting a lot of efforts and resources to control alcohol consumption through policies like National Alcohol Control Policy. However alcohol consumption is still affecting many people in Uganda especially the youths. Therefore the researcher recommended that there should be more policies and interventions for systematic control of alcohol consumption among the youths.
Thesis